Ocean's Twelve - Pitt, Brad, 1963-; Zeta-Jones, Catherine, 1969-; Clooney, George; Ed, Kross; Julia Roberts; Tiffany, Don.; Jacques, Anne.; Sontag, David; Sontag, Larry; Andy, Garcia; Affleck, Casey; Connolly, Dina.; et al. (USA, 2004)
Set three years after "Ocean's 11," this sequel shows us Danny Ocean gathering up his complete gang of con artists and thieves from the first film in New York City before they all jet off to Amsterdam, Rome, and Paris to pull off three seperate heists. All the while, the boys must deal with increasing pressure from a very mad Terry Benedict, a dedicated Europol agent with a link to Rusty's past, and a mysterious French rival known as the "Night Fox." Will Ocean's crew reach their full potential and become the greatest thieves the world has ever known, or will they fall victim to Benedict's revenge? All bets are off.
Three years after pulling an impossible heist of a three-casino vault Daniel Ocean's Eleven plus wife Tess have been found and fingered by Terry Benedict. Mr. Benedict has promised the provider of the information to show restraint and give the clan two weeks to repay him with interest to the tune of over $190 million. Without a job that can provide that kind of pay off, the gang must accept the challenge of premier thief Francois Toulour to see who can steal a famous work of art first and claim the title of greatest thief ever.
Three years after ripping off casino owner Terry Benedict in Las Vegas, Danny Ocean and his gang have settled down. Until the revenge-seeking Benedict contacts them all one-by-one with this: pay back what you stole from me, with interest, or else. They have two weeks to come up with $190 million dollars. In addition to the swiftly approaching deadline, they have to dodge tenacious Europol agent Isabel Lehiri and out-maneuver another thief known only as "The Night Fox." It all culminates in Ocean's 12 taking on the biggest heist ever...and also the biggest con!
This sequel finds itself after the Ocean's 11 Las Vegas casino heist. However, now we find our characters in a hurry to do another heist because Terry Benedict (Garcia) wants his money back. However, when they get to their destination in Europe, they find that the job has already been done by a thief known as the Night Fox, who is out to prove that he's better than Danny Ocean (Clooney) and his Ocean's 11. So, now the group finds theirselves in a race against the clock to find out who can be the best theives of the world.
Three years after Danny Ocean and 10 other thieves managed to steal $160,000,000 from casino tycoon Terry Benedict, they have been caught, and are left with two weeks to give back all the money they stole, plus interest over three years. Danny and his friends needs to get $190,000,000 or else they will be killed, so they plan to pull off three large-scale robberies in Paris, Rome and Amsterdam before the time is up.
Twelve is the new eleven
Keywords: Comedy; Crime; Thriller